Trudne relacje Polski z Palestyną - Siekiera, Joanna (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2017)
Description of the legal and political relations between Poland and the State of Palestine appears significant from international law point of view, as well as contemporary international relations. According to the public international law criteria, Palestine is not yet included to the sovereign actors on global arena. Thus, de jure, relationship between Warsaw and Ramallah cannot be characterized in a similar matter as other diplomatic relations between sovereign entities. Another key issue is the political affiliation of Poland globally. Here, one needs to pay attention on economic, historical and social relations with Israel, the main antagonist of establishment the independent Palestinian state. This implies some certain unilateral acts by Warsaw. The efforts held by the authorities in Ramallah towards the status of the UN observer, and consequently the Polish reaction during the General Assembly vote in 2012 show indeed uneasy relations between these countries
Keywords: Palestyna; Państwo Palestyńskie; polityka zagraniczna; Polska; stosunki dyplomatyczne; relacje polsko-palestyńskie; Izrael